Use of hydrogen storage in an off-grid system for implementing a renewable-energy system. Issue 4 (23rd October 2021) - Noro, Yasuhiro; Uchiyama, Satoshi
Abstract: This paper presents the purpose, advantages, system constitution, operation method and estimation results of using hydrogen storage in a small-scale electric power (off-grid) system when renewable energy sources are introduced. It is assumed that all electricity is supplied from renewable energy sources without using a diesel generator that requires fossil fuels. In other words, for a small-scale electric power system on a remote island, a power-supply system comprising a photovoltaic power-generation system, storage battery, hydrogen-production system, storage tank and a fuel cell is considered. The condition under which the total construction cost is minimized by considering the equipment capacity, operation method of the battery and fuel cell as parameters is investigated. The results demonstrate that the construction cost can be reduced by applying the method of surplus magnification and hydrogen storage. The initial cost is ~70% when hydrogen storage is added as compared with the case in which a storage battery alone is used. Such a cost-effective system can contribute to Japan's self-reliance with regard to the energy sector in the future. Abstract : A small-scale electric power system on a remote island is simulated to find the most economic configuration. The system supplies 10 MW of electricity and comprises a photovoltaic power-generation system, storage battery, hydrogen production and storage system and a fuel cell. Graphical Abstract: